Computational modeling of ventricular-ventricular interactions suggest a role in clinical conditions involving heart failure - Kim, Salla M.; Randall, E. Benjamin; Jezek, Filip; Beard, Daniel A.; Chesler, Naomi C. (Frontiers in Physiology, 2023)
The left (LV) and right (RV) ventricles are linked biologically, hemodynamically, and mechanically, a phenomenon known as ventricular interdependence. While LV function has long been known to impact RV function, the reverse is increasingly being realized to have clinical importance. Investigating ventricular interdependence clinically is challenging given the invasive measurements required, including biventricular catheterization, and confounding factors such as comorbidities, volume status, and other aspects of subject variability. Computational modeling allows investigation of mechanical and hemodynamic interactions in the absence of these confounding factors. Here, we use a three-segment biventricular heart model and simple circulatory system to investigate ventricular interdependence under conditions of systolic and diastolic dysfunction of the LV and RV in the presence of compensatory volume loading. We use the end-diastolic pressure-volume relationship, end-systolic pressure-volume relationship, Frank-Starling curves, and cardiac power output as metrics. The results demonstrate that LV systolic and diastolic dysfunction lead to RV compensation as indicated by increases in RV power. Additionally, RV systolic and diastolic dysfunction lead to impaired LV filling, interpretable as LV stiffening especially with volume loading to maintain systemic pressure. These results suggest that a subset of patients with intact LV systolic function and diagnosed to have impaired LV diastolic function, categorized as heart failure with preserved ejection fraction (HFpEF), may in fact have primary RV failure. Application of this computational approach to clinical data sets, especially for HFpEF, may lead to improved diagnosis and treatment strategies and consequently improved outcomes. This is a provisional file, not the final typeset article.Cardiac power output CVS Cardiovascular system DBP Arterial diastolic blood pressure DD Diastolic dysfunction EDP End-diastolic pressure EDV End-diastolic volume EDPVR End-diastolic pressure-volume relationship ESP End-systolic pressure ESV End-systolic volume ESPVR end-systolic pressure-volume relationship HF Heart failure HFrEF Heart failure with reserved ejection fraction HFpEF Heart failure with preserved ejection fraction HFmrEF Heart failure with mid-range ejection fraction HR Heart rate LW Left ventricular free wall LV Left ventricle M Moderate RW Right ventricular free wall RV Right ventricle S Severe SBP Arterial systolic blood pressure SD Systolic dysfunction SW Septal wall TriSeg Three-segment biventricular model VVI Ventricular-ventricular interactions